Production of Fruiting Body and Antioxidant Activity of Wild Pleurotus - Henny Sulistiany; Lisdar Idwan Sudirman; Okky Setyawati Dharmaputra (Bogor Agricultural University, Indonesia, 2016)
The HS isolate of wild Pleurotus is a wood-rotting fungus found in Bogor, Indonesia. This study was conducted to determine the growth and fruiting body production of HS isolate on three types of substrates, antioxidant activities, and total phenolic contents (TPCs). HS isolate was grown on Paraserianthes falcataria sawdust (PFS substrates), oil palm empty fruit bunch (EFB) substrates, and mixture of PFS and EFB substrates (M substrates) with proportion 1:1, respectively. Analysis of antioxidant activity of mycelial and fruiting body extracts was conducted using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, whereas TPCs were conducted using Folin–Ciocalteu method. The results showed that HS isolate could grow and produce fruiting bodies on all substrates, but based on all observation parameters, M substrates were the best ones for the growth and fruiting body production of HS isolate with biological efficiency of 88.86%. Fruiting body extract of HS isolate had a better ability to reduce DPPH free radical (IC50, 0.45 ± 0.04 mg/mL) with total phenolic compound of fruiting body extract being higher (4.62 ± 0.08 mg gallic acid equivalent/g extract) than those of mycelia extract. Based on this study, HS isolate is potential as a source of natural antioxidants.